COMPARATIVE OVERVIEW OF WORLD FESTIVALS OF VIDEOMAPPING AND VIDEOPROJECTION ARTS - Габрель, Т. М.; Ковальчук, І. В. (Art and Design, 2023)
The goal: to conduct a comparative analysis of world festivals of videomapping and projection art, to establish regularities and trends, to generalize according to the stylistic direction of the events, and to form recommendations for holding similar events in Ukraine. Methodology. The research used the empirical method of describing festivals from literary sources and the Internet, as well as the method of comparative analysis. The results. The main data on festivals of videomapping and videoprojection art were analyzed and systematized, which made it possible to track the key statistical information characterizing them. The analysis was performed according to the following characteristics: city and country of the event, year of establishment, duration, presence of a competitive component, number of visitors and the first and final event, number of installations, participants and represented countries at the last festival. It has been established that video mapping festivals are usually supported by sponsorships and often their profitability is debatable. The main purpose of holding such festivals is to reveal the tourist potential of cities, enrich their cultural life, illuminate their history with modern means of artistic creativity, and integrate the local community of artists into the global creative community. Based on the obtained data, it can be argued that the use of immersive technologies against the background of a virtually arbitrary environment can significantly increase the tourist potential of cities and settlements in general. Scientific novelty. For the first time, a comparative analysis of videomapping festivals in Ukrainian art history literature was conducted with the aim of obtaining quantitative and qualitative data. Practical significance. Based on the obtained data, it is possible to interpolate the patterns of world videomapping festivals to the realities of post-war Ukraine and to involve young artists and the world community of media artists for the full-scale disclosure of the tourist potential of Ukrainian cities by means of immersive technologies.